Feasibility Study of Diploma III Analyst of Health in Department of Nutrition Politeknik Kesehatan Depkes Semarang - Surati Surati; Soesanto Soesanto; Sri Hetty Susetyorini (Jurnal LINK, 2013)
In order to develop Politeknik Depkes Semarang and participate in development efforts particularly in terms of health tretment to maximizing all potentials of existing in Politeknik therefore need to add new major in Politeknik which preceded the implementation of appropriateness studyof Diploma III health analyst.Feasibility study conducted in campus III Department of Nutrition by analyzing the necessary of Department of Analyst in terms of availability of facilities and infrastructure and SDM in the Department of Nutrition and carry out comparative study to Department of Health Analyst in Central Java.Feasibility study of Diploma III Analyst of Health in Department of Nutrition Politeknik Kesehatan Semarang which has general purpose to develop Department of Health Analyst in Poltekkes Depkes Semarang and participate in development efforts in terms of health tretment. And the main purpose is developing Poltekkes Depkes Semarang by adding Development of Health Analyst and maximizing all potentials that has been possessed by Poltekkes Depkes Semarang.SDM ( lecturer ) in Department of Nutrition from first semester until second semester are 66% as lecturer in Department of Health Analyst and only 34% as lecturer from the other institution. Lecturer consists of : 23 permanent lecturers, 6 temporary lecturers, 6 administrations, 11 labor contracts, 4 security (2 PNS and 2 labor contracts) and facilities and infrastructure of education in Department of Health Analyst Poltekkes Depkes Semarang involves: land area and status: 24.629 m owned by Department of Health.Utilization of class room in Department of Nutrition everyday maximum 6 hours so it is still able to used for Department of Health Analyst for class room. Utilization of laboratory room in Department of Nutrition everyday maximum 4 hours  so it is still able to used for Department of Health Analyst for laboratory practice. It takes additional clinical laboratory, hematologi, all equipments and additional class room, secretarial room for administration and management staff of Department of Health Analyst. Diploma III Department of Health Analyst is worthy established in Department of Nutrition.